Pengaruh Metode Pembelajaran Problem Solving Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam - Jon Iskandar Bahari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the influence of applying problem solving learning methods on student learning outcomes in the class X Islamic Cultural History subject. The type of research used is quantitative research using a Pre-Experimental design (one-group-pretest-posttest Design). The population in this study was 253 and the sample in this study was 53. The sampling technique used by researchers was Cluster Sampling. The research results obtained based on the results of the paired samples t-test analysis obtained a sig value. (2-tailed) of 0.000 with a significance level of α=0.05, which means 0.000 <0.05, so Ha is accepted and Ho is rejected. Meanwhile, it is known that the data df=31, the significance level α=0.05, the t-count value = 24.002 and the t-table = 2.021 so it can be stated that the t-count value is greater than the t-table meaning 24.002>2.021 with a correlation level of 0.960 . So Ha is accepted and Ho is rejected, meaning the influence of problem solving learning methods on student learning outcomes in SKI subjects in class is -0.041 (experimental class posttest = 84.84 and control class posttest = 59.05) which means the average score for the experimental class posttest is higher than the control class posttest. Thus it can be concluded that the problem solving method influences student learning outcomes in the SKI class X MAN 3 Banyuwangi subject.